Tess’s Language and Her Victimization: Speech Act Theory in Tess of the d'Urbervilles - Fatemeh Azizmohamadi (Critical Literary Studies)
The present study aims to investigate speech acts in Thomas Hardy’s Tess of the d'Urbervilles based on John Austin’s theory. In the present research, the researcher attempts to investigate female characters’ speech acts in the selected novel at three levels of locutionary act, illocutionary act, perlocutionary act. Austin theories have been published in the book titled How to Do Things with Words which introduces speech acts. The philosophers believes that language is used to display the world. In other words, it shows what exists and what does not exist. The same mechanism can be traced and studied in Tess’s speech acts. It might be claimed that for Tess, the language is not the means of transferring meanings. It is a tool through which their psyche, identity, and the course of their life can be constructed. Using linguistic theories in analyzing the selected work can both depict new aspects of the novel and give insights to the linguists. It can be concluded that the speech acts are the reason why Tess fails in the society and have tragic destiny and the link between the characters’ language and psyche would be detected.